2013
DOI: 10.1002/art.37965
|View full text |Cite
|
Sign up to set email alerts
|

Class I Histone Deacetylase Inhibition Modulates Metalloproteinase Expression and Blocks Cytokine‐Induced Cartilage Degradation

Abstract: Objective. To examine the ability of a broadspectrum histone deacetylase (HDAC) inhibitor to protect cartilage in vivo, and to explore the effects of class-selective HDAC inhibitors and small interfering RNA (siRNA)-induced knockdown of HDACs on metalloproteinase expression and cartilage degradation in vitro. Cartilage destruction in osteoarthritis (OA) is mediated by the action of proteinases from the matrix metalloproteinase (MMP) and ADAMTS families. The pathology of OA has been proposed to be driven by cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 39 publications
5
80
0
1
Order By: Relevance
“…Indeed, various studies have shown the protective effect of HDACi on cartilage degeneration using a collagen antibodyeinduced arthritis or destabilization of the medial meniscus mouse model of OA. 30,31 To our knowledge, all of the reported HDACi have been shown to down-regulate catabolic gene expression in chondrocytes but are not able to alter anabolic gene expression, especially the expression of COL2A1 and ACAN. In this study, we found that SAHA could potentially restore the chondrocyte anabolic gene expression by downregulating the inflammatory cytokine and MMP expression and up-regulating the expression of anabolic markers COL2A1 and ACAN under pathologic conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, various studies have shown the protective effect of HDACi on cartilage degeneration using a collagen antibodyeinduced arthritis or destabilization of the medial meniscus mouse model of OA. 30,31 To our knowledge, all of the reported HDACi have been shown to down-regulate catabolic gene expression in chondrocytes but are not able to alter anabolic gene expression, especially the expression of COL2A1 and ACAN. In this study, we found that SAHA could potentially restore the chondrocyte anabolic gene expression by downregulating the inflammatory cytokine and MMP expression and up-regulating the expression of anabolic markers COL2A1 and ACAN under pathologic conditions.…”
Section: Discussionmentioning
confidence: 98%
“…29 Treatment with TSA, valproic acid, or MS-275 blocks the cytokine-induced expression of MMP-1 and -13 in human articular chondrocytes. 30 Another HDACi, ITF2357, which inhibits class I and II HADCs, reduced the expression of proinflammatory cytokines in synovial tissues, but the mechanisms are not fully clear. 31,32 Therefore, it is plausible that the inhibition of HDACs may have a beneficial effect on the management of OA.…”
Section: Discussionmentioning
confidence: 99%
“…The primary human chondrocytes were isolated from articular cartilage of OA patients undergoing total knee replacement surgery as previously described [16]. Briefly, harvested cartilage was minced into small pieces and incubated in a trypsin-containing solution for 2 h at 37°C.…”
Section: Isolation and Culture Of Chondrocytesmentioning
confidence: 99%
“…Moreover, HDACs, HDAC-1, -2, -3, and -7, regulate Mmp13 expression. Inhibition of these HDACs protects the cartilage destruction induced by IL-1 (interleukin-1), suggesting the potential therapeutic use of HDAC inhibitors for cytokine-induced cartilage degradation observed in OA [56,57].…”
Section: Histone Acetylationmentioning
confidence: 98%